Anaerobic digestion of ammonia-pretreated corn stover. (January 2015) - Yuan, Hairong; Li, Rongping; Zhang, Yatian; Li, Xiujin; Liu, Chunmei; Meng, Ying; Lin, Meina; Yang, Ziyi
Abstract : The effect of ammonia pretreatment on the anaerobic digestibility of corn stover was investigated. Corn stover with different moisture contents (30%, 50%, 70%, and 90%) was pretreated with three concentrations of ammonia (2%, 4%, and 6%) at 35 ± 2 °C for the following batch digestion. Results showed that the reagent of 4% ammonia and 70% moisture content could achieve the highest anaerobic digestibility. In comparison with the untreated, the time needed to produce 90% of the maximum digester gas production ( T 90 ) shortened from 52 d to 37 d. The total biogas production and the unit volatile solids (VS) biogas yield were 20, 740 ml and 427.1 ml respectively, both 26.70% higher than the untreated. It was found that the digesters with high moisture contents of 70% and 90% were more stable and had shorter acidification periods relative to the low moisture contents of 30% and 50%. The decreases in cellulose, hemicelluloses and lignin indicated that ammonia pretreatment could destroy the lignocellulose (LCH) structure and furthermore enhance the biogas production. Following anaerobic digestion, 80.6% of cellulose and 68.52% of hemicelluloses were consumed where there was 4% ammonia and 70% moisture content, indicating why these conditions produced the highest level of biogas. Highlights: Digestibility of different ammonia additions and moisture contents investigated. Changes of main compositions before and after ammonia pretreatment explored. Pretreatment time and VS conversion rate were studied in batch tests.